A Role for a Highly Conserved Protein of Unknown Function in Regulation of Bacillus subtilis purA by the Purine Repressor - Rappu, Pekka (American Society for Microbiology (ASM), 1999)
Regulation of the purine biosynthetic gene purA was examined by using a transcriptional fusion to a luciferase reporter gene. Transcription was repressed about 10-fold by the addition of adenine and increased approximately 4.5-fold by the addition of guanosine. This regulation is mediated by a purine repressor (PurR). In a purR mutant, basal expression was increased 10-fold, and there was no further stimulation by guanosine or repression by adenine. An open reading frame, yabJ, immediately downstream from purR was found to have a role in the repression of purA by adenine. Repression by adenine was perturbed in a purR(+) yabJ mutant, although guanosine regulation was retained. Mutations in the PurR PRPP binding motif abolished guanosine regulation in the yabJ mutant. Thus, PRPP appears to be required for upregulation by guanosine. The amino acid sequence of YabJ is homologous to the YER057c/YjgF protein family of unknown function.